Minorities today - Katz, William Loren (Austin, TX : Raintree/Steck Vaughn, 1993)
Discusses the role of minorities and women in American history and society in this century's last decade, focusing on the experiences of Hispanic Americans, new European immigrants, Asian Americans, Native Americans, and others.
Includes bibliographical references (p. 94) and index.
Horn Book.
Voice of Youth Advocates (V.O.Y.A.).
Wilson's Junior High School.
7-9
Young Adult
Keywords: Minorities -- United States -- Juvenile literature; Civil rights movements -- History -- 20th century; Minorities -- History -- 20th century; Race relations; Civil rights movements -- History; Minorities -- History; Race relations; United States -- Ethnic relations -- Juvenile literature; United States -- Race relations -- Juvenile literature; United States -- History -- 1969-; United States -- History